Spatial And Temporal Analysis Of Heavy Metals Distribution In Sungai Perai - Azhar, Aqilah (Universiti Sains Malaysia, 2021)
Heavy metals are common components on the surface water, however their concentrations were dramatically changed. This study aims to determine the spatial distribution of heavy metals in Sungai Perai to identify the areas with a high concentration of heavy metals and evaluate the temporal analysis of heavy metals in Sungai Perai in the correlation between the concentration of heavy metals and the tidal effects. Industrial areas surround Sungai Perai, and it is the reason it was selected as the case study. The concentration of heavy metals was determined using ICP-OES, while ArcGIS Pro Software was used to generate spatial distribution maps and Microsoft Excel was used to analyze the concentration value of heavy metals. Based on the study, the spatial distribution of heavy metals in Sungai Perai has shown that high concentrations of iron are detected at P1, P2 and P3 during low tide and high tide. A high concentration of copper was spotted at P2, P4, P9 and P10 during the low tide and P12 during the high tide. P1, P2 and P3 have shown a high concentration of zinc during the low tide and meanwhile, P2 has revealed a high concentration during the high tide. A high concentration of lead is noticed at P1 during the low tide and P13 and P14 during the high tide. Lastly, Manganese has shown a high concentration at P5 during the low tide and P2, P4, P5, P6 and P7 for the high tide. For temporal analysis, for iron, the sampling points that do not comply with Class IV are at P9 during low tide and P10 during high tide. For copper, during high tide, the sampling locations which do not comply with Class IV are P7 and P12. Then for zinc, the sampling points that do not comply with Class IIA is at P4 during low tide. Lastly is Manganese, during high tide the sampling points that do not comply with Class IV are at P2 and P7.